Father's Involvement in Children's Distance Learning during the Pandemic - Setiawan, Deni; Aisyah Durrotun Nafisah; Diana (Program Studi Magister Pendidikan Anak Usia Dini, 2022)
The involvement of fathers in children's distance learning is very necessary, considering that Indonesia is included in the third fatherless country category. The purpose of this study was to find out how much the child's response to the father's involvement in children's distance learning was affected during the pandemic. By using a quantitative descriptive survey research design, the sample for this study was sixty-eight children. Data collection techniques include observation, questionnaires, interviews, and documentation. The results from this study are that the children's response to father involvement in children's distance learning during the pandemic is in the high category, which includes aspects of paternal engagement, accessibility, and responsibility. Engaging in children's learning can be seen as an important part of the responsibility. The results of this study help provide support for fathers to be involved in educating and educating their children in a way that is appropriate to the cultural context and current situation. Keywords: distance learning, early childhood, father involvement References: Amini, M. (2015). Profil Keterlibatan Orang Tua [Profile of Parents Involvement in The Education]. Jurnal Ilmiah Visi Pptk Paudni, 10(1), 9–20. Ancell, K. S., & Bruns, D. A. (2018). The Importance of Father Involvement in Early Childhood Programs. Young Exceptional Children, 21(1), 22–33. Aries, P. (1962). Centuries Of Childhood. Translated By R. Baldick. Asy, H., & Ariyanto, A. (2019). Gambaran Keterlibatan Ayah Dalam Pengasuhan Anak (Paternal Involvement) Di Jabodetabek. Intuisi: Jurnal Psikologi Ilmiah, 11(1), 37–44. Https://Doi.Org/10.15294/Intuisi.V11i1.20115 Aziza, F. N., & Yunus, M. (2020). Peran Orang Tua Dalam Membimbing Anak Pada Masastudy from Home Selama Pandemi Covid 19. Konferensi Nasional Pendidikan, 19–21. Bicchieri, C. (2017). Norms In the Wild: How to Diagnose, Measure, And Change Social Norms. Connor, L. A., & Stolz, H. E. (2022). Child Development Knowledge and Father Engagement: The Mediating Role of Parenting Self-Efficacy. Journal Of Family Issues, 43(3), 831–851. Https://Doi.Org/10.1177/0192513x21994628 Craig, A. G., Thompson, J. M. D., Slykerman, R., Wall, C., Murphy, R., Mitchell, E. A., & Waldie, K. E. (2021b). The Father I Knew: Early Paternal Engagement Moderates the Long-Term Relationship Between Paternal Accessibility and Childhood Behavioral Difficulties. Journal Of Family Issues, 42(10), 2418–2437. Https://Doi.Org/10.1177/0192513x20980128 Creswell, J. W. (2003). Research Design: Qualitative, Quantitative, And Mixed Methods Approaches. Sage Publications. Ferreira, T., Cadima, J., Matias, M., Vieira, J. M., Leal, T., & Matos, P. M. (2016). Preschool Children’s Prosocial Behavior: The Role of Mother–Child, Father–Child and Teacher–Child Relationships. Journal Of Child and Family Studies, 25(6), 1829–1839. Https://Doi.Org/10.1007/S10826-016-0369-X Fitzsimons, E., & Villadsen, A. (2019). Father Departure and Children’s Mental Health: How Does Timing Matter? Social Science and Medicine, 222, 349–358. Handarini. (2020). Pembelajaran Daring Sebagai Upaya Study from Home (SFH) Selama Pandemi Covid 19 Pembelajaran Daring Sebagai Upaya Study from Home (SFH) … ... Jurnal Pendidikan Administrasi Perkantoran (Jpap), 8(1), 496–503. Huerta, M., Adema, W., Baxter, J., Jui Han, W., Lausten, M., & Lee, R. (2013). Fathers’ Leave, Fathers’ Involvement and Child Development: Are They Related? Evidence From Four Oecd Countries. Directorate For Employment, Labour and Social Affairs, Employment, Labour, And Social Affairs Committee. Lamb, M. E. (2010). The Role of The Father in Child Development. Wiley. Https://Books.Google.Co.Id/Books?Id=Dlpokmwsu-Qc Liu, X. (2019). A Review of The Study on Father Involvement in Child Rearing. Asian Social Science, 15(9), 82. Liu, Y., Dittman, C. K., Guo, M., Morawska, A., & Haslam, D. (2021). Influence Of Father Involvement, Fathering Practices and Father-Child Relationships on Children in Mainland China. Journal Of Child and Family Studies, 30(8), 1858–1870. Https://Doi.Org/10.1007/S10826-021-01986-4 Mathwasa, J., & Okeke, C. I. O. (2017). Educators’ Perspectives on Fathers’ Participation in The Early Childhood Education of Their Children. International Journal of Educational Sciences, 13(2), 172–185. Https://Doi.Org/10.1080/09751122.2016.11890451 Mccaig, J. L., Stolz, H. E., Reimnitz, S. J., Baumgardner, M., & Renegar, R. G. (2021a). Determinants Of Paternal Engagement: Investigating Low-Income Fathers’ Caregiving, Play, And Verbal Engagement with Infants. Journal Of Family Issues, 0(0), 1–21. Https://Doi.Org/10.1177/0192513x211031515 Mil, S., Jalal, F., & Djamaris, M. (2022). Parenting Fathers for Children During the Pandemic: Lessons Learned from Indonesia. Budapest International Research and Critics Institute-Journal (Birci-Journal), 5(2), 14462–14470. Nangle, S., Kelley, M., Fals-Stewart, W., & Levant, R. (2003). Work And Family Variables as Related to Paternal Engagement, Responsibility, And Accessibility in Dual-Earner Couples with Young Children. Fathering: A Journal of Theory, Research, And Practice About Men as Fathers, 1(1), 71–90. Https://Doi.Org/10.3149/Fth.0101.71 Nasution, I. S. (2020). Peran Orang Tua Terhadap Anak Dalam Program Belajar Dari Rumah Di Masa Pandemi Covid-19. Jurnal Visipena, 11(2), 266–280. Nofianti, R. (2020). Daring Anak Usia Dini di Masa Pandemic Covid 19 Di Tk Islam Ibnu Qoyyim. Jurnal Ilmiah Abdi Ilmu, 13(2), 19–30. Norman, H. (2017). Paternal Involvement in Childcare: How Can It Be Classified and What Are the Key Influences? Families, Relationships and Societies, 6(1), 89–105. Https://Doi.Org/10.1332/204674315x14364575729186 Opondo, C., Redshaw, M., & Quigley, M. A. (2017). Journal Of a Ff Ective Disorders Association Between Father Involvement and Attitudes In Early Child-Rearing And Depressive Symptoms In The Pre-Adolescent Period In A Uk Birth Cohort. Journal Of Affective Disorders, 221, 115–122. Https://Doi.Org/10.1016/J.Jad.2017.06.010 Papaleontiou - Louca, E., & Al Omari, O. (2020). The (Neglected) Role of The Father in Children’s Mental Health. New Ideas in Psychology, 59, 100782. Pertiwi, L. K., Febiyanti, A., & Rachmawati, Y. (2021). Keterlibatan Orang Tua Terhadap Pembelajaran Daring Anak Usia Dini Pada Masa Pandemi Covid-19. 12(1), 19–30. Prasetyaningtyas. (2020). Pelaksanaan Belajar Dari Rumah (BDR) Secara Online Selama Darurat Covid-19 Di Smp N 1 Semin. Ideguru: Jurnal Karya Ilmiah Guru, 5(1), 86–94. Raghavan, R., & Alexandrova, A. (2014). Toward A Theory of Child Well-Being. Social Indicators Research, 1–16. Recto, P., Lesser, J., Moreno-Vasquez, A., Zapata, J., & Zavala Idar, A. (2021). Supporting The Mental Health Needs of Adolescent Fathers During Covid-19: Opportunities for Nursing Practice and Community-Based Partnerships. Issues In Mental Health Nursing, 42(7), 702–705. Rogoff, B., Sellers, M., Pirrotta, S., Fox, N., & White, S. (1975). Age Of Assignment of Roles and Responsibilities in Children: A Cross-Cultural Survey. Human Development, 18, 353–369. Sipahutar. (2018). Interaksi Anak Dengan Orang Tua Dalam Mengatasi Kesulitan Belajar Di Kampung Kurnia Kelurahan Belawan Bahari, Kecamatan Medan Belawan Tahun 2018. Director, 15(40), 6–13. Skipp, A., V. Hopwood, and R. W. (2021). Special Education in Lockdown: The Experiences of School and College Providers and Families of Pupils with Education, Health, and Care Plans (Ehcp’s). Online Nuffield Foundation. Skjothaug, T., Smith, L., Wentzel-Larsen, T., & Moe, V. (2018). Does Fathers’ Prenatal Mental Health Bear A Relationship to Parenting Stress At 6 Months? Infant Mental Health Journal, 39(5), 537–551. Sugiyono. (2011). Metode Penelitian Kuantitatif, Kualitatif Dan Kombinasi (Mixed Methods). Tétreault, É., Bernier, A., & Matte-Gagné, C. (2021). Quality Of Father-Child Relationships as A Predictor of Sleep Developments During Preschool Years. Developmental Psychobiology, 63(6), 1–13. Https://Doi.Org/10.1002/Dev.22130 Trumello, C., Bramanti, S. M., Lombardi, L., Ricciardi, P., Morelli, M., Candelori, C., Crudele, M., Cattelino, E., Baiocco, R., Chirumbolo, A., & Babore, A. (2021). Covid-19 And Home Confinement: A Study on Fathers, Father-Child Relationships and Child Adjustment. Child: Care, Health and Development, February 1–7. Https://Doi.Org/10.1111/Cch.12912 Volker J. (2014). Paternal Involvement: A Review of The Factors Influencing Father Involvement and Outcomes. Tcnj J Stud Scholars, 16. Walsh, A. D., Hesketh, K. D., Van Der Pligt, P., Cameron, A. J., Crawford, D. A., & Campbell. (2017). Fathers‟ Perspectives on The Diets and Physical Activity Behaviours Of Their Young Children. Plos One, 12(6), 1–19. Widi. (2020). Kendala Dan Peran Orangtua Dalam Pembelajaran Daring Pada. Seminar Nasional Pascasarjana 2020, 471–479.